Comparative Study on Crp An Inflammatory Biomarkers in Type 2 Diabetes Mellitus - Merina A, Sahaya; N, Kiruthika; Thankam V. S, Rani; Varghese, Angel; Kumar T , Senthil; Raman K, Thulasi (Journal of Neonatal Surgery, 2025)
Background:The main objective of this study is to prove that CRP level is higher in T2DM cases comparing to non- diabetic which may lead to heart disease among the patients Methods: A cross-sectional study was conducted from November 2023 to May 2024, using the blood samples of the patients of type II diabetes mellitus patients, analysed in Agappe nephlometer for CRP and Beckman coulter AU480 for blood sugar and HbA1c. Results:A total of 100 patients samples are taken for Hba1c, CRP, FBS&PPBS for the study of High level CRP in Diabetic Patients. Out of the 100 apparently (Diabetic 50 sample Non-Diabetic 50 sample) patients Conclusions:The study concludes that the Type II Diabetes Mellitus patients have increased Crp level than the Non-Diabetic patients.It can be concluded from the study that raised levels of plasma CRP in type 2 diabetic patients may contribute to ongoing atherosclerotic processes leading to the development of coronary heart disease in these patients and this can be used as a early marker of development of atherosclerosis in patients with diabetes mellitus.